Regorafenib-Induced Hand–Foot Skin Reaction Is More Severe on the Feet Than on the Hands - Nonomiya, Yuma (Oncol Res, 2019)
Regorafenib is a multikinase inhibitor for the treatment of metastatic colorectal cancer. Regorafenib-induced hand–foot skin reaction (HFSR) is a common side effect during treatment. The reported frequency of HFSR was 80% (grade 3: 28%) in the Japanese subpopulation in the CORRECT trial; however, more detailed data regarding HFSR in terms of onset and sites of susceptibility are unclear. Additionally, the risk factors for regorafenib-induced severe HFSR are unknown. The aim of this study was to compare HFSR between the hands and feet and identify preexisting risk factors for severe HFSR in Japanese patients receiving regorafenib. We retrospectively examined the onset and severity of HFSR on the hands and feet of patients with metastatic colorectal cancer treated with regorafenib from May 2013 to October 2015 in the Cancer Institute Hospital of the Japanese Foundation for Cancer Research. In addition, we examined the possible association between preexisting clinical factors and severe HFSR. Our results showed that no significant difference in the incidence of HFSR of any grade was observed between the hands (71%) and feet (74%) (p = 0.63). The incidence of grade 3 HFSR was more frequent on the feet (33%) than on the hands (8%) (p < 0.01). The onset of grade 3 HFSR was earlier on the feet than on the hands (p < 0.001). No preexisting risk factor was identified. Our findings indicate that severe HFSR was more prevalent on the feet than on the hands, suggesting the need for appropriate screening for early detection and treatment of regorafenib-induced HSFR.